Rethinking research in the medical humanities: a scoping review and narrative synthesis of quantitative outcome studies. Issue 3 (March 2016) - Dennhardt, Silke; Apramian, Tavis; Lingard, Lorelei; Torabi, Nazi; Arntfield, Shannon
Abstract : Objectives: The rise of medical humanities teaching in medical education has introduced pressure to prove efficacy and utility. Review articles on the available evidence have been criticised for poor methodology and unwarranted conclusions. To support a more nuanced discussion of how the medical humanities work, we conducted a scoping review of quantitative studies of medical humanities teaching. Methods: Using a search strategy involving MEDLINE, EMBASE and ERIC, and hand searching, our scoping review located 11 045 articles that referred to the use of medical humanities teaching in medical education. Of these, 62 studies using quantitative evaluation methods were selected for review. Three iterations of analysis were performed: descriptive, conceptual, and discursive. Results: Descriptive analysis revealed that the medical humanities as a whole cannot be easily systematised based on simple descriptive categories. Conceptual analysis supported the development of a conceptual framework in which the foci of the arts and humanities in medical education can be mapped alongside their related epistemic functions for teaching and learning. Within the framework, art functioned as expertise, as dialogue or as a means of expression and transformation. In the discursive analysis, we found three main ways in which the relationship between the arts and humanities and medicine was constructed as, respectively, intrinsic, additive and curative. Conclusions: This review offers a nuanced framework of how different types of medical humanities work. The epistemological assumptions and discursive positioning of medical humanities teaching frame the forms of outcomes research that are considered relevant to curriculum decision making, and shed light on why dominant review methodologies make some functions of medical humanities teaching visible and render others invisible. We recommend the use of this framework to improve the rigor and relevance of future explorations of the efficacy and utility of medical humanities teaching. Abstract : Discuss ideas arising from the article athttp://www.mededuc.com discuss.